A closer look at the relationships between aspects of connectedness and flourishing - Rahe, Martina; Jansen, Petra (Frontiers in Psychology, 2023)
Everyone strives for personal happiness or well-being. Flourishing is a broader concept of well-being. To better understand which factors are associated to people’s flourishing, we took a closer look at the relationships of flourishing with three aspects of connectedness: Connectedness with oneself (self-love), with others (pro-socialness), and with the surrounding nature (nature connectedness). Participants were 138 adults between 18 and 71 years (M = 23.21, SD = 7.90, 98 women, 40 men). Significant positive correlations were found between flourishing and self-love and between flourishing and pro-socialness. Furthermore, nature connectedness correlated positively with self-love and with pro-socialness. A regression analysis revealed that all predictors explained 57.5% of the variance of the criterion flourishing. Self-love and pro-socialness were significant predictors of flourishing while nature connectedness was not. One explanation for the large correlations between self-love and flourishing could be overlapping aspects in both questionnaires. The fact that pro-socialness is a stronger predictor than nature connectedness could be due to a more reciprocal reinforcement of pro-social behavior. If a person treats another well, s/he is more likely treated well by that person which could reflect flourishing. Such a direct reciprocal relationship does not exist with nature.